2020
DOI: 10.24953/turkjped.2020.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Temporal bone hemangioendothelioma as a rare vascular tumor in childhood: case report and review of the literature

Abstract: Background. Hemangiondothelioma is a rare vascular tumor that can occur in the bone. Temporal bone involvement has been reported extremely rare in the literature. Case. Radiological examination of a one-year-old girl who was admitted due to facial paralysis revealed vascular tumor of the temporal bone and Galen vein aneurysm. Pathological examination showed retiform hemangioendothelioma. She was treated with propranolol, prednisolone, vincristine, and endovascular embolization followed by oral sirolimus. With … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…[ 96 ] A review of the literature revealed five cases of reported primary intracranial RHE [ Table 3 ]. [ 1 , 34 , 44 , 89 ] There is a wide age range (1–62 years of age), with a slight female predilection (3:2). Four of the five cases showed tumors originating in bone.…”
Section: Discussionmentioning
confidence: 99%
“…[ 96 ] A review of the literature revealed five cases of reported primary intracranial RHE [ Table 3 ]. [ 1 , 34 , 44 , 89 ] There is a wide age range (1–62 years of age), with a slight female predilection (3:2). Four of the five cases showed tumors originating in bone.…”
Section: Discussionmentioning
confidence: 99%
“…Drug responsiveness of emergent KMP cannot be accurately predicted. These different mechanisms of anti-tumor action and reduced likelihood of ---------------------------------------------------------------------------------------------------------------------- drug-resistance to cocktail therapy may render it a promising alternative (12,13). The present study, with more patients than the 2018 study by Cashell et al (12), demonstrated significant response and good tolerance of cocktail therapy with the triad combination of prednisolone, VCR and sirolimus for infants with KMP.…”
Section: Discussionmentioning
confidence: 99%
“…However, drugs resistance has led to KMP patients being in critical conditions for longer time periods (7)(8)(9)(10). Results from cocktail therapy used for acquired immunodeficiency syndrome (11) and triad therapy for KHE (12,13) suggest that cocktail therapy with prednisolone, VCR and sirolimus may be a more efficient treatment for KMP and may help to avoid prednisolone, VCR, or sirolimus resistance and accelerate the improvement of coagulopathy, thereby reducing KMP infant mortality. The present study evaluated the efficacy of the triad combination of prednisolone, VCR and sirolimus as cocktail therapy of life-threatening KMP in 10 infant patients.…”
Section: Introductionmentioning
confidence: 99%